Composite film with super hydrophobic and EMI shielding properties and preparation method and application thereof
Through the preparation method of AgNWs/PLA/Fe3O4 composite film, the problem of easy hydrolysis of PLA-based EMI shielding composite material in humid environments is solved, and the superhydrophobic and excellent EMI shielding performance of the composite film is achieved, which is suitable for electronic device shielding materials in humid environments.
Patent Information
- Application Number
- CN202310194085.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-03-03
AI Technical Summary
Existing biodegradable PLA-based EMI shielding composites are prone to hydrolysis in humid environments, resulting in structural collapse and affecting their shielding performance and service life.
AgNWs/PLA/Fe3O4 composite film was prepared by polyol method, and AgNWs were dispersed in ethanol, and gradually dripped into PLA/Fe3O4 composite solution. After drying at room temperature, a composite film with superhydrophobic and EMI shielding properties was prepared by modification of triethoxy-1H, 1H, 2H, 2H-tridefluoro-n-octylsilane.
The asymmetric porous structure of the composite membrane is realized, and its superhydrophobic properties and EMI shielding properties are improved. The water contact angle reaches 150.2° and the EMISET can reach 50.8dB. It is suitable for shielding materials for electronic devices in humid environments.
Smart Images

Figure CN116200020B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrophobic and electromagnetic shielding composite materials, in particular to a composite film with super hydrophobic and EMI shielding properties, and a preparation method and application thereof. Background Art
[0002] According to domestic and foreign research, polymer-based EMI shielding composite materials are mainly divided into two types: petroleum-based and biodegradable EMI shielding composite materials. However, petroleum-based EMI shielding composite materials are difficult to degrade, and they are easily polluted when discarded in the environment after use. From the perspective of the development of green materials, biodegradable EMI shielding composite materials have great research value. PLA, as a biodegradable material with abundant sources, has been widely studied as a PLA-based composite film for EMI shielding, but it is inevitable that there is a problem that hydrolysis in a humid environment during use will cause structural collapse, affecting its shielding performance and service life. Therefore, it is necessary to carry out structural design to make the biodegradable PLA-based EMI shielding composite material have excellent hydrophobic properties. Summary of the invention
[0003] The invention provides a preparation method of a composite film with super hydrophobicity and EMI shielding performance and application thereof, aiming to make up for the deficiencies of the prior art.
[0004] The present invention adopts the following technical solutions to achieve the invention objectives:
[0005] A composite film with super hydrophobicity and EMI shielding performance is provided, wherein the composite film is an AgNWs / PLA / Fe3O4 composite film.
[0006] The method for preparing the aforementioned composite film having super hydrophobicity and EMI shielding performance comprises the following steps:
[0007] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0008] Step S2: preparing AgNWs by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0009] Step S3: gradually dripping the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and drying at room temperature to prepare a semi-finished AgNWs / PLA / Fe3O4 composite film;
[0010] Step S4: The AgNWs / PLA / Fe3O4 composite membrane semi-finished product prepared in step S3 is modified by triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane (TTO) to obtain an AgNWs / PLA / Fe3O4 composite membrane.
[0011] The aforementioned method for preparing a composite film having super-hydrophobic and EMI shielding properties, the method for preparing the PLA / Fe3O4 composite solution in step S1 comprises the following steps:
[0012] Step S11: weighing a certain mass ratio of L-polylactic acid and D-polylactic acid and dissolving them in dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, to obtain a composite PLA solution;
[0013] Step S12: weigh a certain amount of Fe3O4 powder, add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine for ultrasonic dispersion, and prepare a PLA / Fe3O4 composite solution.
[0014] The aforementioned method for preparing a composite film with superhydrophobic and EMI shielding properties, wherein in step S11, the mass ratio of left-handed polylactic acid to right-handed polylactic acid is 8:1-10:1, and the total amount is 0.8-1.2 g; the amount of dichloromethane is 18-22 mL, and the stirring speed is 1500-2000 rpm; in step S12, the amount of Fe3O4 is 45-55 mg, and the ultrasonic time is 0.8-1.2 min.
[0015] The method for preparing the composite film having super-hydrophobic and EMI shielding properties, the method for preparing the AgNWs dispersion in step S2 comprises the following steps:
[0016] Step S21: adding FeCl3·6H2O to ethylene glycol, and dispersing the mixture by magnetic stirring, and adding polyvinyl pyrrolidone, and dispersing the mixture by magnetic stirring to obtain solution A;
[0017] Step S22: Adding AgNO3 into ethylene glycol, stirring with a magnetic stirrer to completely dissolve and evenly disperse the AgNO3, to obtain solution B;
[0018] Step S23: adding solution A dropwise into solution B, stirring magnetically, transferring to a high-pressure reactor for hydrothermal treatment, and cooling to room temperature;
[0019] Step S24: centrifugally washing with acetone and ethanol in sequence, taking out the lower layer of precipitate and dispersing it in ethanol to obtain an AgNWs dispersion.
[0020] The preparation method of the composite film with super-hydrophobic and EMI shielding properties is as follows: in step S21, 0.66-0.72 mg of FeCl3·6H2O is added to 38-42 mL of ethylene glycol, and the mixture is dispersed by magnetic stirring for 4-6 min, and 0.69-0.73 g of polyvinyl pyrrolidone is added, and the mixture is dispersed by magnetic stirring for 18-22 min; in step S22, the amount of AgNO3 is 0.63-0.73 g, and the amount of ethylene glycol is 38-42 mL; in step S23, the mixture is magnetically stirred for 8-12 min, and the hydrothermal treatment conditions are 150-170°C for 2-3 h; in step S24, the washing times of acetone and ethanol are 1-3 and 3-5 respectively, and the washing is performed until the upper liquid becomes clear; and the stirring speed in steps S21, S22 or S23 is 1300-1700 rpm.
[0021] In the aforementioned method for preparing a composite film with superhydrophobic and EMI shielding properties, the content of AgNWs in step S3 accounts for 0-6wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite film semi-finished product; in the AgNWs / PLA / Fe3O4 composite film, the mass percentage of Fe3O4 is 4-5wt%.
[0022] The above-mentioned method for preparing a composite film with superhydrophobic and EMI shielding properties, the specific steps of the modification are: in the S step 4, 0.28-0.32g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane is dissolved in 9.5-9.9g of ethanol to hydrolyze it, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product, shaken for 0.3-0.7h, and taken out for natural drying.
[0023] The aforementioned application of the composite film having super-hydrophobic and EMI shielding properties uses the composite film as a shielding material for electronic devices in a humid environment. Beneficial Effects
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention proposes a method for synthesizing an AgNWs / PLA / Fe3O4 composite membrane in one step by a non-solvent induced phase separation method, wherein a uniform PLA / Fe3O4 composite solution is prepared by dissolving left-handed polylactic acid and right-handed polylactic acid in dichloromethane and adding Fe3O4 powder; then, an AgNWs / ethanol solution prepared by a polyol method is dropwise added into the PLA / Fe3O4 composite solution, and an AgNWs / PLA / Fe3O4 composite membrane semi-finished product is obtained by drying at room temperature, and then a final AgNWs / PLA / Fe3O4 composite membrane is prepared by dip coating with a triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane / ethanol solution; the raw materials used in the present invention are not modified or treated in any way, and an AgNWs / PLA / Fe3O4 composite membrane having both superhydrophobicity and EMI shielding performance can be prepared by a one-step method, and the process operation is simple, the time cost is low, and it is easy to mass produce.
[0026] 2. The AgNWs / PLA / Fe3O4 composite membrane provided by the present invention has an asymmetric porous structure. On the one hand, the porous structure and surface synapses make the main contribution to the superhydrophobicity of the composite membrane, and the superhydrophobicity is further improved after TTO coating; on the other hand, the asymmetric porous structure in which the upper layer is constructed with AgNWs to construct a thermal conductive network and the interior is uniformly distributed with Fe3O4 gives the composite membrane excellent EMI shielding performance.
[0027] 3. When the AgNWs and Fe3O4 contents of the AgNWs / PLA / Fe3O4 composite film provided by the present invention are about 5wt% and 4.53wt% respectively, the water contact angle (WCA) is as high as 150.2°, and the average electromagnetic interference shielding effectiveness (EMISE T ) can reach 50.8dB, and can be used as EMI shielding material for electronic devices in humid environments, which is conducive to expanding the application market of PLA.
[0028] 4. The PLA matrix used in the present invention has a wide range of sources and is biodegradable. The preparation process is simple to operate, has low time cost, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the AgNWs prepared in the present invention.
[0030] Figure 2 This is the XRD pattern of silver AgNWs prepared in the present invention.
[0031] Figure 3 This is the surface SEM image of the AgNWs / PLA / Fe3O4 composite film prepared in the present invention.
[0032] Figure 4This is a cross-sectional SEM image of the AgNWs / PLA / Fe3O4 composite film prepared in the present invention.
[0033] Figure 5 The water contact angles of the AgNWs / PLA / Fe3O4 composite films with different AgNWs contents prepared in the present invention.
[0034] Figure 6 The conductivity and resistivity of the AgNWs / PLA / Fe3O4 composite films with different AgNWs contents prepared by the present invention.
[0035] Figure 7 The EMI shielding performance of the AgNWs / PLA / Fe3O4 composite films with different AgNWs contents prepared by the present invention in the X-band (8.2-12.4GHz).
[0036] Figure 8 The total electromagnetic interference shielding performance, reflected electromagnetic interference shielding performance and absorbed electromagnetic interference shielding performance of the AgNWs / PLA / Fe3O4 composite films with different AgNWs contents prepared by the present invention. Implementation
[0037] In order to enable those skilled in the art to better understand the solution of the present invention, the following will be clearly and completely described through the technical solution in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0038] Example 1. An AgNWs / PLA / Fe3O4 composite film.
[0039] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0040] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0041] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 9:1, adding them into 20 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 1750 rpm to obtain a composite PLA solution;
[0042] Step S12: Weigh 50 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240W for 1 minute to obtain a uniform PLA / Fe3O4 composite solution.
[0043] The Fe3O4 added in this step accounts for 4.53wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0044] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0045] Specifically, step S21: dissolving 0.69 mg FeCl3·6H2O in 40 mL ethylene glycol, and dispersing the mixture under magnetic stirring for 5 min, adding 0.71 g polyvinyl pyrrolidone, and dispersing the mixture under magnetic stirring for 20 min to obtain solution A;
[0046] Step S22: Add 0.68 g of AgNO3 into 40 mL of ethylene glycol, and stir with a magnetic stirrer for 10 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0047] Step S23: adding solution A dropwise into solution B, stirring magnetically for 10 min, transferring to a high-pressure reactor for hydrothermal treatment at 160° C. for 2.5 h, and cooling to room temperature;
[0048] The stirring speed in step S21, S22 or S23 is 1500 rpm.
[0049] Step S24: Use acetone and ethanol to perform centrifugal washing 1 and 4 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0050] Step S3: gradually dripping 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and preparing an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in the step S3 accounts for 1 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0051] Step S4: 0.3 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.7 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.5 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties, which was marked as 1-AgNWs / PLA / Fe3O4.
[0052] Comparative Example: The difference between this embodiment and Example 1 is that the content of AgNWs in step 3 is 0 wt %, and the other steps and parameters are the same as those in Example 1, and the sample is marked as 0-AgNWs / PLA / Fe3O4.
[0053] Example 2. An AgNWs / PLA / Fe3O4 composite film.
[0054] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0055] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0056] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 9:1, adding them into 20 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 1750 rpm to obtain a composite PLA solution;
[0057] Step S12: Weigh 50 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240W for 1 minute to obtain a uniform PLA / Fe3O4 composite solution.
[0058] The Fe3O4 added in this step accounts for 4.53wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0059] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0060] Specifically, step S21: dissolving 0.69 mg FeCl3·6H2O in 40 mL ethylene glycol, and dispersing the mixture under magnetic stirring for 5 min, adding 0.71 g polyvinyl pyrrolidone, and dispersing the mixture under magnetic stirring for 20 min to obtain solution A;
[0061] Step S22: Add 0.68 g of AgNO3 into 40 mL of ethylene glycol, and stir with a magnetic stirrer for 10 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0062] Step S23: adding solution A dropwise into solution B, stirring magnetically for 10 min, transferring to a high-pressure reactor for hydrothermal treatment at 160° C. for 2.5 h, and cooling to room temperature;
[0063] The stirring speed in step S21, S22 or S23 is 1500 rpm.
[0064] Step S24: Use acetone and ethanol to perform centrifugal washing 1 and 4 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0065] Step S3: gradually drip 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and prepare an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in the step S3 accounts for 2 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0066] Step S4: 0.3 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.7 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.5 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties, which was marked as 2-AgNWs / PLA / Fe3O4.
[0067] Example 3. An AgNWs / PLA / Fe3O4 composite film.
[0068] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0069] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0070] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 9:1, adding them into 20 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 1750 rpm to obtain a composite PLA solution;
[0071] Step S12: Weigh 50 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240W for 1 minute to obtain a uniform PLA / Fe3O4 composite solution.
[0072] The Fe3O4 added in this step accounts for 4.53wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0073] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0074] Specifically, step S21: dissolving 0.69 mg FeCl3·6H2O in 40 mL ethylene glycol, and dispersing the mixture under magnetic stirring for 5 min, adding 0.71 g polyvinyl pyrrolidone, and dispersing the mixture under magnetic stirring for 20 min to obtain solution A;
[0075] Step S22: Add 0.68 g of AgNO3 into 40 mL of ethylene glycol, and stir with a magnetic stirrer for 10 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0076] Step S23: adding solution A dropwise into solution B, stirring magnetically for 10 min, transferring to a high-pressure reactor for hydrothermal treatment at 160° C. for 2.5 h, and cooling to room temperature;
[0077] The stirring speed in step S21, S22 or S23 is 1500 rpm.
[0078] Step S24: Use acetone and ethanol to perform centrifugal washing 1 and 4 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0079] Step S3: gradually drip 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and prepare an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in step S3 accounts for 3 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0080] Step S4: 0.3 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.7 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.5 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties, which was marked as 3-AgNWs / PLA / Fe3O4.
[0081] Example 4. An AgNWs / PLA / Fe3O4 composite film.
[0082] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0083] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0084] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 9:1, adding them into 20 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 1750 rpm to obtain a composite PLA solution;
[0085] Step S12: Weigh 50 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240W for 1 minute to obtain a uniform PLA / Fe3O4 composite solution.
[0086] The Fe3O4 added in this step accounts for 4.53wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0087] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0088] Specifically, step S21: dissolving 0.69 mg FeCl3·6H2O in 40 mL ethylene glycol, and dispersing the mixture under magnetic stirring for 5 min, adding 0.71 g polyvinyl pyrrolidone, and dispersing the mixture under magnetic stirring for 20 min to obtain solution A;
[0089] Step S22: Add 0.68 g of AgNO3 into 40 mL of ethylene glycol, and stir with a magnetic stirrer for 10 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0090] Step S23: adding solution A dropwise into solution B, stirring magnetically for 10 min, transferring to a high-pressure reactor for hydrothermal treatment at 160° C. for 2.5 h, and cooling to room temperature;
[0091] The stirring speed in step S21, S22 or S23 is 1500 rpm.
[0092] Step S24: Use acetone and ethanol to perform centrifugal washing 1 and 4 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0093] Step S3: gradually drip 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and prepare an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in the step S3 accounts for 4 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0094] Step S4: 0.3 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.7 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.5 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties, which was marked as 4-AgNWs / PLA / Fe3O4.
[0095] Example 5. An AgNWs / PLA / Fe3O4 composite film.
[0096] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0097] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0098] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 9:1, adding them into 20 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 1750 rpm to obtain a composite PLA solution;
[0099] Step S12: Weigh 50 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240W for 1 minute to obtain a uniform PLA / Fe3O4 composite solution.
[0100] The Fe3O4 added in this step accounts for 4.53wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0101] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0102] Specifically, step S21: dissolving 0.69 mg FeCl3·6H2O in 40 mL ethylene glycol, and dispersing the mixture under magnetic stirring for 5 min, adding 0.71 g polyvinyl pyrrolidone, and dispersing the mixture under magnetic stirring for 20 min to obtain solution A;
[0103] Step S22: Add 0.68 g of AgNO3 into 40 mL of ethylene glycol, and stir with a magnetic stirrer for 10 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0104] Step S23: adding solution A dropwise into solution B, stirring magnetically for 10 min, transferring to a high-pressure reactor for hydrothermal treatment at 160° C. for 2.5 h, and cooling to room temperature;
[0105] The stirring speed in step S21, S22 or S23 is 1500 rpm.
[0106] Step S24: Use acetone and ethanol to perform centrifugal washing 1 and 4 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0107] Step S3: gradually drip 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and prepare an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in the step S3 accounts for 5 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0108] Step S4: 0.3 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.7 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.5 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties, which was marked as 5-AgNWs / PLA / Fe3O4.
[0109] Example 6. An AgNWs / PLA / Fe3O4 composite film.
[0110] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0111] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0112] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 9:1, adding them into 20 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 1750 rpm to obtain a composite PLA solution;
[0113] Step S12: Weigh 50 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240W for 1 minute to obtain a uniform PLA / Fe3O4 composite solution.
[0114] The Fe3O4 added in this step accounts for 4.53wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0115] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0116] Specifically, step S21: dissolving 0.69 mg FeCl3·6H2O in 40 mL ethylene glycol, and dispersing the mixture under magnetic stirring for 5 min, adding 0.71 g polyvinyl pyrrolidone, and dispersing the mixture under magnetic stirring for 20 min to obtain solution A;
[0117] Step S22: Add 0.68 g of AgNO3 into 40 mL of ethylene glycol, and stir with a magnetic stirrer for 10 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0118] Step S23: adding solution A dropwise into solution B, stirring magnetically for 10 min, transferring to a high-pressure reactor for hydrothermal treatment at 160° C. for 2.5 h, and cooling to room temperature;
[0119] The stirring speed in step S21, S22 or S23 is 1500 rpm.
[0120] Step S24: Use acetone and ethanol to perform centrifugal washing 1 and 4 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0121] Step S3: gradually drip 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and prepare an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in the step S3 accounts for 6 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0122] Step S4: 0.3 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.7 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.5 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties, which was marked as 6-AgNWs / PLA / Fe3O4.
[0123] During the research of this invention, a large number of experimental studies were carried out, and some experimental records are shown in Figure 1-8 .
[0124] Depend on Figure 1 It can be seen that the AgNWs prepared in the present invention exhibit obvious linear shapes and smooth surfaces, uniform texture, and no particle impurities.
[0125] like Figure 2 It can be seen that the XRD pattern of the prepared AgNWs shows five characteristic diffraction peaks of elemental Ag at 38.1°, 44.3°, 64.4°, 77.4° and 81.5°, corresponding to the (111), (200), (220), (311) and (222) crystal planes of Ag, respectively, which is consistent with the standard spectrum of silver (JCPDS file, No. 99-0094).
[0126] Combination Figure 1 and Figure 2 The discussion results further prove that the present invention successfully prepared AgNWs.
[0127] Depend on Figure 3 It can be seen that unique microsphere synapses appear on the surface of the AgNWs / PLA / Fe3O4 composite film. Many microsphere synapses are stacked adjacent to each other, which is very similar to the synapses on the surface of lotus leaves. This is mainly due to the strong hydrogen bonding effect between PLLA and PDLA, which promotes the nucleation of stereocomposite crystals, resulting in the consumption of more PLLA molecular chains and the generation of more and smaller synapses in a limited space. The microsphere synapses and the air layer between the microsphere synapses help to give the AgNWs / PLA / Fe3O4 composite film a certain degree of hydrophobicity. In addition, it can be clearly observed that the AgNWs are staggered and overlapped between the microsphere synapses, which can give the composite film excellent conductivity, further making an important contribution to the EMI shielding performance.
[0128] Depend on Figure 4 It can be seen that most of the Fe element is evenly distributed on the cross-section of the AgNWs / PLA / Fe3O4 composite film, and only a very small part is agglomerated at the bottom; at the same time, the distribution of the Ag element increases rapidly from the lower layer to the upper layer of the cross-section, and is mainly deposited on the upper layer of the cross-section; this shows that Fe3O4 is almost evenly distributed inside the composite film, while AgNWs are mainly distributed on the surface of the composite film, which is conducive to the formation of an excellent conductive network. This asymmetric porous structure not only contributes to the low density and light weight of the composite film, but also is beneficial to multiple reflections and absorption losses of EMI.
[0129] Depend on Figure 5 It can be seen that the AgNWs / PLA / Fe3O4 composite films modified by TTO all show excellent water contact angles, all around 150°. In particular, the water contact angle (WCA) of the 5-AgNWs / PLA / Fe3O4 composite film is as high as 150.2°, which can achieve a superhydrophobic effect. This is the result of the surface microsphere synapses formed on the surface of the composite film and the low surface energy TTO modification.
[0130] Depend on Figure 6 It can be seen that the conductivity of the AgNWs / PLA / Fe3O4 composite film increases with the increase of the AgNWs content. When the AgNWs content is 5wt%, the conductivity can reach 1.08x10 4S / m, far exceeding the conductivity (1S / m) required for EMI shielding materials in practical applications, thanks to the conductive network constructed by AgNWs. However, when the AgNWs content reaches 6wt%, the conductivity drops sharply. This is because during the preparation of the composite film, excessive high aspect ratio AgNWs are prone to aggregation, and due to their own weight, some AgNWs will be embedded in the PLA, which is not conducive to the AgNWs building an effective conductive network on the surface of the composite film. This discussion shows that when the AgNWs filling content is 5wt%, the conductivity of the AgNWs / PLA / Fe3O4 composite film prepared by the present invention is optimal.
[0131] Depend on Figure 7 It can be seen that under the synergistic effect of Fe3O4 and AgNWs, the average total electromagnetic interference shielding effectiveness (EMISE T ) increases with the increase of AgNWs filling content, and reaches a peak value of 50.3dB when the content is 5wt%. This is caused by the magnetic loss and conductivity loss of electromagnetic waves caused by the magnetic Fe3O4 and the AgNWs network with excellent conductivity, respectively. In addition, the asymmetric porous structure increases the transmission path of electromagnetic waves, thereby increasing the loss of electromagnetic waves, so that the composite film achieves excellent EMI shielding performance. It is particularly noted that the EMI shielding performance of the AgNWs / PLA / Fe3O4 composite film prepared by the present invention is not ideal when the AgNWs filling content is low (1wt%) or high (6wt%). This is because the low content of AgNWs is not enough to build an effective conductive network on the surface of the composite film, and the high content of AgNWs is easy to aggregate and embed into the interior of the composite film during the phase separation process, thereby affecting the formation of the conductive network on the surface of the composite film.
[0132] Combination Figure 6 and Figure 7 The discussion results further prove that the AgNWs / PLA / Fe3O4 composite film prepared by the present invention has the best hydrophobicity and EMI shielding performance when the filling contents of Fe3O4 and AgNWs are 4.53wt% and 5wt% respectively. It is the best sample of the present invention and can be used as a shielding material for electronic devices in humid environments.
[0133] Depend on Figure 8 It can be seen that the average absorption electromagnetic interference shielding effectiveness (EMISE) of AgNWs / PLA / Fe3O4 composite films with different AgNWs addition amounts A ) are greater than the average reflected electromagnetic interference shielding effectiveness (EMISE R), indicating that the shielding of electromagnetic waves by the composite film prepared by the present invention is mainly based on absorption, which is due to the multiple reflections of electromagnetic waves in the asymmetric porous structure and the magnetic loss of electromagnetic waves by Fe3O4 and the gradual movement of charge carriers on the conductive network constructed by AgNWs.
[0134] Example 7. An AgNWs / PLA / Fe3O4 composite film.
[0135] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0136] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0137] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 8:1, adding them to 18 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 1500 rpm to obtain a composite PLA solution;
[0138] Step S12: Weigh 45 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240 W for 0.8 min to obtain a uniform PLA / Fe3O4 composite solution.
[0139] The Fe3O4 added in this step accounts for 4wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0140] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0141] Specifically, step S21: dissolving 0.66 mg FeCl3·6H2O in 38 mL ethylene glycol, stirring and dispersing for 4 min under magnetic stirring, adding 0.69 g polyvinyl pyrrolidone, stirring and dispersing for 18 min under magnetic stirring, to obtain solution A;
[0142] Step S22: Add 0.63 g of AgNO3 into 38 mL of ethylene glycol, and stir with a magnetic stirrer for 8 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0143] Step S23: adding solution A dropwise into solution B, stirring magnetically for 8 min, transferring to a high-pressure reactor for hydrothermal treatment at 150° C. for 2 h, and cooling to room temperature;
[0144] The stirring speed in step S21, S22 or S23 is 1300 rpm.
[0145] Step S24: Use acetone and ethanol to perform centrifugal washing 2 and 3 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0146] Step S3: gradually drip 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and prepare an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in the step S3 accounts for 2.5 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0147] Step S4: 0.28 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.5 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.3 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties.
[0148] Comparative Example: The difference between this embodiment and Example 1 is that the content of AgNWs in step 3 is 0 wt %, and the other steps and parameters are the same as those in Example 1, and the sample is marked as 0-AgNWs / PLA / Fe3O4.
[0149] Example 8. An AgNWs / PLA / Fe3O4 composite film.
[0150] The preparation method of AgNWs / PLA / Fe3O4 composite film is as follows:
[0151] Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution;
[0152] Specifically, step S11: weighing 1 g of L-polylactic acid and D-polylactic acid with a mass ratio of 10:1, adding them into 22 mL of dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, and stirring at a speed of 2000 rpm to obtain a composite PLA solution;
[0153] Step S12: Weigh 50 mg of Fe3O4 powder and add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine and ultrasonically disperse it at 240 W for 1.2 min to obtain a uniform PLA / Fe3O4 composite solution.
[0154] The Fe3O4 added in this step accounts for 5wt% of the mass of the AgNWs / PLA / Fe3O4 composite film prepared later.
[0155] Step S2: preparing AgNWs with excellent conductive properties by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion;
[0156] Specifically, step S21: dissolving 0.72 mg FeCl3·6H2O in 42 mL ethylene glycol, and dispersing the mixture under magnetic stirring for 6 min, adding 0.73 g polyvinyl pyrrolidone, and dispersing the mixture under magnetic stirring for 22 min, to obtain solution A;
[0157] Step S22: Add 0.73 g of AgNO3 into 42 mL of ethylene glycol, and stir with a magnetic stirrer for 12 min to completely dissolve and evenly disperse the AgNO3 to obtain solution B;
[0158] Step S23: adding solution A dropwise into solution B, stirring magnetically for 12 min, transferring to a high-pressure reactor for hydrothermal treatment at 170° C. for 3 h, and cooling to room temperature;
[0159] The stirring speed in step S21, S22 or S23 is 1700 rpm.
[0160] Step S24: Use acetone and ethanol to perform centrifugal washing 3 and 5 times respectively, take the lower layer of precipitate and disperse it in 3 mL of ethanol to prepare AgNWs dispersion.
[0161] Step S3: gradually drip 3 mL of the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and prepare an AgNWs / PLA / Fe3O4 composite membrane semi-finished product by drying at room temperature; the content of AgNWs in the step S3 accounts for 1.5 wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite membrane semi-finished product.
[0162] Step S4: 0.32 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane was dissolved in 9.9 g of ethanol for alcoholysis, and then immersed in the AgNWs / PLA / Fe3O4 composite film semi-finished product and gently shaken manually for 0.7 h to obtain an AgNWs / PLA / Fe3O4 composite film with superhydrophobic and EMI shielding properties.
[0163] The equipment and raw materials involved in the present invention are all prior art, and those skilled in the art can directly purchase and use them. The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite film with super hydrophobic and EMI shielding properties, characterized in that: The composite film is an AgNWs / PLA / Fe3O4 composite film; The method for preparing the composite membrane comprises the following steps: Step S1: preparing a composite PLA solution, and then adding Fe3O4 powder to prepare a uniform PLA / Fe3O4 composite solution; Step S2: preparing AgNWs by a polyol method, and dispersing the AgNWs in ethanol to prepare an AgNWs dispersion; Step S3: gradually dripping the AgNWs dispersion prepared in step S2 into the PLA / Fe3O4 composite solution prepared in step S1, and drying at room temperature to prepare a semi-finished AgNWs / PLA / Fe3O4 composite film; Step S4: modifying the AgNWs / PLA / Fe3O4 composite membrane semi-finished product prepared in step S3 by triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane to obtain an AgNWs / PLA / Fe3O4 composite membrane; The method for preparing the PLA / Fe3O4 composite solution in step S1 comprises the following steps: Step S11: weighing a certain mass ratio of L-polylactic acid and D-polylactic acid and dissolving them in dichloromethane, stirring them with a magnetic stirrer to completely dissolve and evenly disperse them, to obtain a composite PLA solution; Step S12: weigh a certain amount of Fe3O4 powder, add it to the composite PLA solution prepared in step S11, put it into an ultrasonic cleaning machine for ultrasonic dispersion, and prepare a PLA / Fe3O4 composite solution; In the step S11, the mass ratio of L-polylactic acid to D-polylactic acid is 8:1-10:1, and the total amount is 0.8-1.2 g; the amount of dichloromethane is 18-22 mL, and the stirring speed is 1500-2000 rpm; in the step S12, the amount of Fe3O4 is 45-55 mg, and the ultrasonic time is 0.8-1.2 min.
2. A method for preparing a composite film having super hydrophobicity and EMI shielding properties as claimed in claim 1, characterized in that: The method for preparing the AgNWs dispersion in step S2 comprises the following steps: Step S21: adding FeCl3·6H2O to ethylene glycol, and dispersing the mixture by magnetic stirring, and adding polyvinyl pyrrolidone, and dispersing the mixture by magnetic stirring to obtain solution A; Step S22: Adding AgNO3 into ethylene glycol, stirring with a magnetic stirrer to completely dissolve and evenly disperse the AgNO3, to obtain solution B; Step S23: adding solution A dropwise into solution B, stirring magnetically, transferring to a high-pressure reactor for hydrothermal treatment, and cooling to room temperature; Step S24: Use acetone and ethanol to perform centrifugal washing in sequence, take out the lower layer of precipitate and disperse it in ethanol to obtain an AgNWs dispersion.
3. A method for preparing a composite film having super hydrophobicity and EMI shielding performance as described in claim 2, characterized in that : In the step S21, 0.66-0.72 mg of FeCl3·6H2O is added to 38-42 mL of ethylene glycol, and the mixture is dispersed by magnetic stirring for 4-6 min, and 0.69-0.73 g of polyvinyl pyrrolidone is added and dispersed by magnetic stirring for 18-22 min; in the step S22, the amount of AgNO3 is 0.63-0.73 g, and the amount of ethylene glycol is 38-42 mL; in the step S23, the mixture is magnetically stirred for 8-12 min, and the hydrothermal treatment conditions are 150-170° C. for 2-3 h; in the step S24, the washing times of acetone and ethanol are 1-3 and 3-5 respectively, and the mixture is washed until the upper layer becomes clear; the stirring speed in the steps S21, S22 or S23 is 1300-1700 rpm.
4. A method for preparing a composite film having super hydrophobicity and EMI shielding properties as claimed in claim 1, characterized in that: The content of AgNWs in step S3 does not exceed 6wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite film semi-finished product, and is not 0wt%; in the AgNWs / PLA / Fe3O4 composite film, the mass percentage of Fe3O4 is 4-5wt%.
5. A method for preparing a composite film having super hydrophobicity and EMI shielding properties as claimed in claim 4, characterized in that: The content of AgNWs in the step S3 accounts for 5wt% of the mass percentage of the AgNWs / PLA / Fe3O4 composite film semi-finished product; in the AgNWs / PLA / Fe3O4 composite film, the mass percentage of Fe3O4 is 4.53wt%.
6. A method for preparing a composite film having super hydrophobic and EMI shielding properties as claimed in claim 1, characterized in that: In step S4, 0.28-0.32 g of triethoxy-1H, 1H, 2H, 2H-tridecafluorooctylsilane is dissolved in 9.5-9.9 g of ethanol to perform alcoholysis, and then the semi-finished AgNWs / PLA / Fe3O4 composite membrane is immersed in the semi-finished product, shaken for 0.3-0.7 h, and taken out to dry naturally.
7. Use of the composite film having super hydrophobicity and EMI shielding properties as claimed in any one of claims 1 to 6, characterized in that: The composite film is used as a shielding material for electronic devices in a humid environment.
Citation Information
Patent Citations
Mussel bionic polylactic acid multilayer composite antibacterial film, preparation method and application thereof
CN111218019A
Low-reflection and high-absorption porous electromagnetic shielding device and preparation method thereof
CN113561473A